7z-4=3z+2

Simple and best practice solution for 7z-4=3z+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7z-4=3z+2 equation:


Simplifying
7z + -4 = 3z + 2

Reorder the terms:
-4 + 7z = 3z + 2

Reorder the terms:
-4 + 7z = 2 + 3z

Solving
-4 + 7z = 2 + 3z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-3z' to each side of the equation.
-4 + 7z + -3z = 2 + 3z + -3z

Combine like terms: 7z + -3z = 4z
-4 + 4z = 2 + 3z + -3z

Combine like terms: 3z + -3z = 0
-4 + 4z = 2 + 0
-4 + 4z = 2

Add '4' to each side of the equation.
-4 + 4 + 4z = 2 + 4

Combine like terms: -4 + 4 = 0
0 + 4z = 2 + 4
4z = 2 + 4

Combine like terms: 2 + 4 = 6
4z = 6

Divide each side by '4'.
z = 1.5

Simplifying
z = 1.5

See similar equations:

| 15d^4/3d^9 | | f(x)=-16x^2-8x+26 | | 1=9x/6x-11 | | Lnx^2=ln(x+20) | | 2*x^3+6*x^2-24*x+12=0 | | 28-(9/2) | | 2+8x=2-8x | | 28-(9/29 | | 3x+23+3x-1=46-3x+39 | | x/14=16 | | 6z-1=6z+1 | | 1.66666667x+10=15 | | 6z-1=6z | | x^2=-18+11x | | x^2=-18+11 | | 14x-53+32x=73 | | 3=(v-14)^1/4 | | m-(4+2m)=2m+2 | | 5(x+2)-(4n+3)= | | 46x-63-25x=-174 | | 6/15=2/c= | | 1.25+x=2.5(2-x) | | x+1=30-x | | 2x^2-12x=10 | | 3xn=6 | | S^3=24 | | 3xm+2xn= | | 4x^2-17x-108=0 | | -14=25-3x | | -3=1x | | 7(-a-3)+5a+6= | | 9-9.45=-10.6 |

Equations solver categories